Social preferences on networks - Bastian Westbrock; Stephanie Rosenkranz; Sarah Rezaei; Utz Weitzel (ZBW - Leibniz Information Centre for Economics, 2021)
We develop a model of social preferences for network games and study its predictions in a local public goods game with multiple equilibria. The key feature is that players' social preferences are heterogeneous. This gives room for disagreement between players about the "right" payoff ordering. When preferences are compatible, however, players coordinate on a refined equilibrium set. How easily the requirements for preference compatibility are met crucially depends on a property of the network structure: neighborhood nestedness. This means that equilibrium selection succeeds in small, connected structures but also in centralized networks. All predictions are confirmed in an experiment.
Keywords: D85; C70; C91; H41; 330; social preferences; network games; equilibrium selection